2016
DOI: 10.1111/dme.13257
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction and not glucagon‐like peptide‐1 explains the acute improvement in glucose control after gastric bypass in Type 2 diabetes

Abstract:  The increased weight loss at 7 days following RYGB compared to 7 days of VLCD in T2DM is due to greater loss of lean and water mass  After RYGB, the early and enhanced post-meal rise in glucose and insulin is due to rapid absorption through the gastroenterostomy  The increased post-meal GLP-1 secretion specific to RYGB is not accompanied by an improvement in insulin or glucose AUC when compared to VLCD  The early improvement in glucose control in T2DM after bariatric surgery is not explained by improved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 32 publications
1
53
1
Order By: Relevance
“…Our findings question the role of GLP-1 in the mechanism of longterm diabetes remission. Of note, Steven and colleagues reported that calorie restriction but not GLP-1 explains the acute improvement in glycaemic control following RYGB in subjects with T2DM [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings question the role of GLP-1 in the mechanism of longterm diabetes remission. Of note, Steven and colleagues reported that calorie restriction but not GLP-1 explains the acute improvement in glycaemic control following RYGB in subjects with T2DM [31].…”
Section: Discussionmentioning
confidence: 99%
“…No comparable observations have been made in previous studies, and the pathophysiologic mechanism underlying this requires investigation. GLP-1 responsiveness was not examined in this study and dietary weight loss has previously been shown not to change this after return to non-diabetic glucose control (28,29).…”
Section: Studies Of Rodent Beta Cells In Vitro Suggest a Relatively Rmentioning
confidence: 96%
“…), which occurs prior to any changes in bodyweight or alterations in plasma GLP‐1 levels (Steven et al . ). With only a fraction of individuals accessing surgery, there is a need for other treatment options to help achieve clinically relevant weight loss that may bring about T2D remission.…”
Section: Type 2 Diabetes and Very Low‐energy And Low‐energy Dietsmentioning
confidence: 97%
“…The exact mechanisms which drive improvements in, and remission of, T2D following bariatric surgery remain to be fully understood, although are hypothesised to include alterations in gut hormones, bile acid changes, adaptions in the microbiome and changes in food preferences and smell (Miras & le Roux 2013;Batterham & Cummings 2016). Recent evidence points towards the acute energy restriction that occurs immediately following bariatric surgery playing a pivotal role in the early glycaemic improvements seen in both biliopancreatic diversion (BPD) and Roux-en-Y gastric bypass (RYGB) (Jackness et al 2013;Lips et al 2014), which occurs prior to any changes in bodyweight or alterations in plasma GLP-1 levels (Steven et al 2016b). With only a fraction of individuals accessing surgery, there is a need for other treatment options to help achieve clinically relevant weight loss that may bring about T2D remission.…”
Section: Weight Loss and Type 2 Diabetes Remissionmentioning
confidence: 99%